MPACT OF CUSTOMER SATISFACTION TOWARDS PONDS SKIN CARE PRODUCT IN PERAMBALUR TOWN - Kavitha, Mrs.J.; Santhi, Prof.R. (IJRDO - Journal of Applied Management Science, 2017)
This study attempts to investigate the factors thatinfluence the purchase intention of femalecustomers towards skin care productsspecialreferance with Perambalur town of Tamilnadu.A total of 60 current customers using cosmeticswere approached to collect data, by means ofquestionnaires. They were analyzed utilizing thedescriptive research technique.The research hasbeen conducted to know the peoples expectationand satisfaction Towards Ponds Skin CareProduct. The difficulties faced by the customerswith regard to skin care products availability andquality were also inquired into and there by theiroverall satisfaction level was studied. This is adescriptive research and mainly primary data isused for the purpose of data collection throughquestionnaire. It was undertaken to determinethe customer opinion and behavior of customers,price, quality, brand name are included in thestudy. Satisfaction level on ponds skin careproducts. Spss package program was used toanalyze the data.